Strengthening Financial Management Skills among OTOP Entrepreneurs through Digital Tools - Soffan, Raden Muhamad; Syafei, M. Yani; Rahayu, Siti Kurnia; Surya, Desayu Eka; Yang, Zhuo; Wannapong, Chanchon; Qudsiy, Asroyuddin El; Maulana⁠, Rendi (PT Inovasi Pratama Internasional, 2025)
This study aimed to strengthen financial management skills among OTOP (One Tambon One Product) entrepreneurs in Bangprong Subdistrict, Bangkok, Thailand, through digital tools. Many OTOP businesses face challenges in maintaining proper financial records, limiting access to external financing. A training program was implemented on August 26, 2025, combining lectures, hands-on practice, consultation, and digital tool simulations using Microsoft Excel.The results showed a significant improvement in participants’ financial literacy, with test scores rising from 48.6% to 82.4%. About 80% of participants successfully completed digital transaction simulations, and 60% continued using these tools after two weeks. Participants reported greater confidence in managing their business finances, though infrastructure and sustained usage remain challenges.The study concludes that digital-based training effectively improves financial literacy and adoption technology, but long-term success requires continuous mentoring, collaboration with stakeholders, and integration of widely used digital platforms.